SOSIALISASI MANFAAT VAKSIN COVID-19 DI LINGKUNGAN PONDOK PESANTREN ASSOHWAH AL-ISLAMIYAH LOMBOK BARAT - Tuhfatul Ulya; Pauzan; Dhika Juliana Sukmana (Bakti Sekawan : Jurnal Pengabdian Masyarakat, 2022)
Covid-19 is a new type of deadly virus. Vaccination is one solution to get out of this pandemic. The emergence of various hoaxes in the community about the Covid-19 vaccine, resulted in a decrease in public interest in carrying out vaccinations. As an effort to make the vaccination program a success, it is necessary to socialize the benefits of vaccines in Islamic boarding schools to facilitate the face-to-face teaching and learning process. The socialization went smoothly and got a good response from the students, seen from the number of students who asked questions related to vaccines.